Beta human chorionic gonadotropin concentrations in serum of patients with pancreatic adenocarcinoma. Issue 1 (1st January 1998) - Syrigos, K N; Fyssas, I; Konstandoulakis, M M; Harrington, K J; Papadopoulos, S; Milingos, N; Peveretos, P; Golematis, B C
Abstract : Background —Human chorionic gonadotropin (hCG) is normally produced and secreted by trophoblastic cells during pregnancy and from gestational trophoblastic neoplasms. It is also detected in ovarian, stomach, and colon adenocarcinomas, as well as in squamous cell carcinoma of the oesophagus. Recently, interest in its role in the pathogenesis of tumours has been enlivened after the presence of βhCG in the cell membrane of several malignant cells was shown in vitro. Aims —To investigate the circulating concentrations of βhCG in patients with exocrine pancreatic adenocarcinoma and to examine its potential prognostic value. Patients —Thirty six patients with exocrine pancreatic adenocarcinoma, 12 patients with chronic pancreatitis, and 21 healthy volunteers were studied. Methods —βhCG serum concentrations were detected by the application of a radioimmunoassay technique. Results —Fifteen of 36 patients with pancreatic adenocarcinoma and only one patient with chronic pancreatitis had detectable plasma concentrations of βhCG (p<0.01). The patients with circulating serum titres of βhCG had a worse outcome compared with the group of βhCG negative patients: the difference was statistically significant (p=0.01). Conclusion —More than 40% of pancreatic exocrine tumours produce βhCG and its production is correlated with an adverse effect on outcome.